If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15 = 12x + 3 + -6x + 4 Reorder the terms: 15 + 10x = 12x + 3 + -6x + 4 Reorder the terms: 15 + 10x = 3 + 4 + 12x + -6x Combine like terms: 3 + 4 = 7 15 + 10x = 7 + 12x + -6x Combine like terms: 12x + -6x = 6x 15 + 10x = 7 + 6x Solving 15 + 10x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 10x + -6x = 7 + 6x + -6x Combine like terms: 10x + -6x = 4x 15 + 4x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + 4x = 7 + 0 15 + 4x = 7 Add '-15' to each side of the equation. 15 + -15 + 4x = 7 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 7 + -15 4x = 7 + -15 Combine like terms: 7 + -15 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| (x-2)/(5)=(4x+2)/(25) | | 174-2x=25x+8 | | 12x+5=6x+9+17x | | (x-7/8)^2-2(x-7/8)+5=0 | | y=-7(-3)+1 | | -4(y-12)= | | x+22=5x | | 9ln(3x)=270 | | (x+54)^2/5=64 | | 0=-32t+28 | | 2-3(6x+3)=4x+2 | | 4x^(3/5)=64 | | 12+2+x=2x+9 | | 2+3(0-1)=0-1 | | 5a-5=-3(-a-1) | | 6x+4=58 | | x^2+10.8x-0.6=0 | | solvex^2+10.8x-0.6=0 | | -1+9-6(1)=12-7(1)-3 | | 5x/6x= | | v^6-64=0 | | x^2+10.8x+0.6=0 | | 0.2b^2+15b-150=0 | | 23-4x=11+8x | | -4y-(5y+6)=3 | | 5/6(7-2)+1/3 | | -5(2x-8)+3x=52 | | 12+2x-6=x+15 | | 12+2x-6=x+16 | | 5x+3=6x+9 | | 3+5q=x+15 | | 4x^3-6x^2-24x= |